ANALISIS MANAJEMEN RISIKO PADA ORGANISASI IKATAN MAHASISWA MUHAMMADIYAH MENGGUNAKAN METODE ANALISIS RISIKO ISO 31000 - celina, aninda; Alda Yasfa Azzahra; Candra Bagus Ainur Rochman; Novie Andriani Zakariya (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
The Muhammadiyah Student Association (IMM) is one of theextra-campus student organizations at Sunan Ampel State Islamic University Surabaya (UINSA). IMM in UINSA was formed in 1989 with the initial formation divided into three commissariats. However, in 1992, with the merger of the Faculty of Ushuluddinand Philosophy into the Faculty of Da'wah and Communicationand the Faculty of Adab and Humanities, IMM expanded to fivecommissariats. Despite this, IMMs often face a variety oforganizational problems. This study aims to explore theapplication of ISO 31000-based risk management to IMM atUINSA. This research will use a qualitative approach withinterviews and observations to identify the risks faced by IMM andevaluate the application of risk management principles based onISO 31000. The aim is to provide a deep understanding of theobstacles, challenges, and potential improvements in theimplementation of risk management in IMM. The results of thestudy will be categorized based on the level of risk: extreme, high, medium, low, and very low. The results of this study identifiedthree main risks in IMM management. First, low communicationeffectiveness can lead to misunderstanding and conflict betweenmembers. Second, emotional challenges hinder collaboration andteamwork due to members' lack of emotional bonds. Third, financial dependence on Muhammadiyah could potentially lead tofinancial instability and limited funds for IMM programs andactivities. Proactive and adaptive risk management strategies are recommended, including implementing a strong communicationstrategy, organizing team-building activities, and diversifyingfunding sources. By deeply understanding these risks, IMM canensure the future viability and success of the organization. Keywords: Risk Analysis, ISO 31000, Risk Management, Qualitative Index Method, Muhammadiyah Student AssociationOrganization